9. THE CURRENT SITUATION OF SLEEP DISORDERS AND SOME RELATED FACTORS IN HEALTH FIELD STUDENTS AT DAI NAM UNIVERSITY (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current status of sleep disorders and some related factors in health students at Dai Nam University in 2022.Research method: The study had a cross-sectional descriptive design using an online survey on 412 health students at Dai Nam University through the Google forms application. Sleep status was measured using the AIS-5 scale.Results: More than 1/3 of students had sleep disorders according to the AIS-5 scale (34.2%). The majority of students do not have problems with falling asleep at night (63.6%), waking up during the night (65.5%), and waking up earlier than desired (62.9%). No students experienced severe nighttime awakenings. However, a high proportion of students felt their total sleep time was significantly (13.4%) or severely (4.4%) lacking. Students who were in a relationship had significantly more sleep disorders (40.6%) than those who were single (32.1%) or married (0%). The rate of sleep disorders was highest among medical students (41.4%), followed by pharmacy students (31.3%), and lowest among nursing students (26.7%). Students who have the habit of watching short videos before bed and have psychological disorders also have a significantly higher rate of sleep disorders.Conclusion: The rate of sleep disorders in Health Sciences students at Dai Nam University is relatively high. Sleep disorders are related to relationship status, field of study, habit of watchingshort videos before bed and psychological disorders. There is a need for health education solutions so that Health Science students have healthy sleeping habits and psychological stability.
Keywords: Sleep disorders, health science students, Dai Nam University, AIS-5.